Gait characteristics in community-dwelling older persons with low skeletal muscle mass and low physical performance - Longobucco, Yari; Krumpoch, Sebastian; Lauretani, Fulvio; Angileri, Valentina; Sieber, Cornel; Marzetti, Emanuele; Calvani, Riccardo; Cherubini, Antonio; Landi, Francesco; Bernabei, Roberto; Freiberger, Ellen; Maggio, Marcello (Aging Clinical and Experimental Research, 2022)
Background Demographic changes in the western world entail new clinical approaches and challenges in older persons. Low skeletal muscle mass and low physical performance in older persons are both predisposing conditions for disability and obtaining knowledge in this cohort is essential. Aim The primary aim of the study was to analyze a broader spectrum of gait characteristics within this specific population and differentiate them across different test conditions. Methods Two centers participating at the SPRINTT project with hi-tech gait analysis available conducted a cross-sectional descriptive study on N = 115 community-dwelling older persons with low muscle mass and physical performance. Reference values of 13 gait parameters were collected across different conditions: usual gait speed, fast gait speed, and usual gait speed while simultaneously naming animals. Results and discussion This study shows the first spatio-temporal reference values in a community-dwelling older population composed of individuals with low skeletal muscle mass and low physical performance. In comparison to the normative spatio-temporal gait parameters in older persons reported in the literature, this population showed some differences. The mean gait speed was lower than 1 m/s, considered as a cutoff for vulnerable community-dwelling individuals, which corresponds to a greater risk of falls, hospitalization, and mortality. The stride length variability was higher, exposing to a greater risk of falling, and was also associated with a higher risk of developing cognitive decline. Conclusion This study represents the first step in the development of quantitative reference values in community-dwelling older persons with low physical performance and low skeletal muscle mass.
CRIS-Team WoS Importer:2022-02-25